2023
DOI: 10.3390/ijms24043072
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Levels Are Associated with Complement C4 Deposits and Interstitial Arteritis in ANCA-Associated Renal Vasculitis

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a potentially life-threatening systemic small-vessel vasculitis that is characterized by pauci-immune glomerulonephritis in case of kidney involvement, representing a major denominator of AAV mortality. Innate immunity with complement system activation is increasingly recognized in the pathogenesis of AAV and as an attractive therapeutic target. Although C-reactive protein (CRP) was thought to be a passive, nonspecific marker of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We have shown that complement C3 deposition in the glomerular tuft is associated with impaired kidney function in ANCA-associated renal vasculitis [12,40]. Independent of consumption of systemic complement components, CRP levels correlated with active renal lesions and intrarenal C4 deposition in interstitial arteries in MPO-ANCA renal vasculitis [41]. We saw an implication for CRP engaging in intrarenal complement synthesis.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We have shown that complement C3 deposition in the glomerular tuft is associated with impaired kidney function in ANCA-associated renal vasculitis [12,40]. Independent of consumption of systemic complement components, CRP levels correlated with active renal lesions and intrarenal C4 deposition in interstitial arteries in MPO-ANCA renal vasculitis [41]. We saw an implication for CRP engaging in intrarenal complement synthesis.…”
Section: Discussionmentioning
confidence: 70%
“…Nuclear counterstaining was performed using Mayer's Hematoxylin Solution (Sigma, St. Louis, MO, USA). C3c and C4d deposits in the glomerular tuft, interlobular arteries, peritubular capillaries, and venules were evaluated for presence, as recently described [12,41].…”
Section: Renal Histopathologymentioning
confidence: 99%
“…Interestingly, a similar pattern can be observed in the case of renal manifestations, even though the difference between subsets of GPA is on the border of significance ( p = 0.05). As CRP is not only a nonspecific biomarker of inflammation but also contributes to forming complement C4 deposits, which play a pivotal role in developing renal manifestations [ 38 ], it can partially explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The literature data conclude that CRP could be of prognostic value in evaluating Chagas autoimmune myocarditis progression, and cardiac dysfunction and remodeling [ 661 , 662 ]. Despite its diagnostic utility, individuals with giant cell arteritis can show disparate CRP results—and there exist reports with normal values—whereas CRP can be increased in autoimmune thrombocytopenia; systemic vasculitis; leukocytoclastic vasculitis; other IgG4-related vascular diseases; polyarteritis nodosa in which it can predict poor outcomes if complications are present; and Henoch–Schönlein purpura, in which it can act as a possible biomarker for gastrointestinal involvement; and it was also reported as a marker in anti-neutrophil cytoplasmic antibody (ANCA)-associated renal vasculitis with interstitial arteritis [ 663 , 664 , 665 , 666 , 667 ]. CRP has been reported to be elevated in both antineutrophil cytoplasmic antibody-negative and -positive eosinophilic granulomatosis with polyangiitis.…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%